Design of an integrated fixed-film activated sludge (IFAS) system for possible application at the Borcherds Quarry WWTW - Kritzinger, Marco (Department of Civil Engineering, 2019)
Nitrification can be seen as the weakness of a conventional activated sludge (CAS) process employing biological nutrient removal (BNR). Suspended nitrifiers only grow in the aerobic zone of the biological reactor but are subjected to anaerobic and anoxic conditions where no nitrifier growth takes place. To establish a nitrifier population that consistently produces low effluent ammonia concentrations, long sludge ages are required (about 15 to 25 days) in South African BNR wastewater treatment plants. This results in relatively large biological reactors. Integrated Fixed-Film Activated Sludge (IFAS) systems have been used extensively in European and Scandinavian countries. This process entails the addition of moving-bed biofilm carriers in certain zones of an activated sludge system to establish biofilm growth. The most successful application has been the addition of these carriers in the aerobic zones of activated sludge plants to facilitate the growth of nitrifiers on the biofilm. This allows nitrifiers to grow independently from the suspended sludge age since it remains stationary on the biofilm in the aerobic tank. The system is thereby relieved from the requirement of a long suspended sludge age. For the University of Cape Town (UCT) process commonly employed in South Africa, it is shown that a suspended sludge age of 5 to 7 days is adequate to meet final effluent standards when converted to an IFAS process. As a result, an UCT-IFAS process can treat 50% to 70% more wastewater in an existing process volume or reduce the size required for a new installation by 30% to 40% when compared to a conventional UCT process with a minimum wastewater temperature of 14°C. The intricacies and challenges associated with designing an IFAS process are unpacked in this thesis to gain a better understanding of what is required to harvest the potential benefits.